Control of induction motors - Trzynadlowski, Andrzej (Academic Press series in engineering.)
This is a reference source for practising engineers specializing in electric power engineering and industrial electronics. It begins with the basic dynamic models of induction motors and progresses to low- and high-performance drive systems.